The Mediating Effect of Job Satisfaction on the Relationship Between Belongingness and Challenging Work Towards Employee Retention - Ishaq Ibrahim Ahmed Bani Melhem (Universiti Sains Islam Malaysia, 2024)
This study investigated the mediation of job satisfaction on the relationship between challenging work and belongingness toward employee retention in the manufacturing industry in Klang Valley. Focusing on the importance of employee retention, this study tested the challenging work effect on employee retention which consists of several constructs such as task identity, skills variety and autonomy. Nevertheless, the effect of belongingness towards employee retention was studied within the constructs of employee loyalty, organizational justice and employee engagement. Survey design was employed with probability simple random sampling method, and questionnaires were distributed to collect data from 750 employees in the industry of the study. A total of 540 responses were collected as returned questionnaires and 480 were usable for the analysis purposes. Quantitative research method was used for the analysis purposes. The statistical package of social science (SPSS) program was used to perform the factor analysis, reliability analysis and descriptive statistical analysis. Analysis of a moment structures (AMOS) program was used to carry out the analysis on structural equation model and to examine the research hypotheses. This study mainly contributes in enhancing the literature of the concept of employee retention, improving the methods of the study in the human resource area, and in finding out the effect of the research factors on employee retention. The study found that belongingness significantly and directly affects employee retention and there is a significant direct effect of job satisfaction as the mediator to the relationship between belongingness and employee retention.Challenging work significantly affects employee retention and there is a significant mediating role of job satisfaction on the relationship between challenging work and employee retention. The study aims to contribute in the body of knowledge of employee retention in the manufacturing sector.